The non-technical skills needed by graduates of technical colleges in metalwork technology - Bakare Shola. F; Azlan Abdul Latib; Rosmah Samari; Yusri Kamin; Muhammad Sukri Saud; Nor Fadila Amin (Institute of Advanced Engineering and Science, 2019)
This studycentered on the views of the professionals about the non-technical skills considered crucial as recruitment prerequisite among graduates of metalwork technology from technical and vocational institutions in Nigeria. It will also examine the possibility of integrating these skills into the curriculum. The study made use of the survey research design. One research question guided the study. The population for the study comprised metalwork technology professionals in Ogun State, Southwestern Nigeria. A 36-item questionnaire was the instrument used for data collection. The instrument was validated by experts from the University of Lagos (UNILAG). The reliability of the instrument was determined using Cronbach Alpha and the reliability index which stood at 0.79. The data collected were analysed using mean statistic and standard deviation. The study revealed that professionals placed great importance on communication skills, problem-solving skills, teamwork skills and self-management qualities among others, as important recruitment prerequisite among graduates of metalwork technology from technical and vocational institutions in Nigeria. The study concludes with the suggestions that non-technical skills should be integrated into the curriculum particularly in the field of metalwork technology in technical colleges. Students should be familiar with the employers’ recruitment criteria while they are still in schools in order to equip them with the necessary skills needed for employment.